THE CONTENT OF LIPIDS IN INTRAMUSCULAR ADIPOSE AS A QUALITY DETERMINANT OF CATTLE MEAT PRODUCT - Wisje L. Toa, Laurentius J.M. Rumokoy & (Proceeding of International Congress, 2014)
Generally consumer taste for meat livestock products related to various aspects of the meat itself that iscommonly known such as, color, tenderness, flavor, hygiene and product information about the animalration that is free of antibiotics, hormones and other substances which interfere the health of consumers.This article aims to describe another aspect which supports the consumerâs taste that is lipids moleculescontent in intramuscular adipose tissue. The higher content of intramuscular lipids will further enhancethe consumer taste of this meat product. The methods to detect intramuscular fat content in meat cattleare enzymatic method. This evaluation of the development of intramuscular adipose tissue and the quantificationof the lipid content can be used as a parameter for determining the quality of meat products ofcattle in improving the organoleptic value of livestock meat products in the market.Keywords: lipids, adipose, intramuscular, cattle meat.